IMPLEMENTASI FUNGSI ORGANIZING PESANTREN DALAM MEMFORMULASIKAN TUPOKSI SDM (KEPENGURUSAN) DI PONDOK PESANTREN MAMBAUL HUDA PUTRI SILIRAGUNG BANYUWANGI - Nahdliyah, Amirotun; Mumarasatul Haqqi, Ika (Proceedings of Annual Conference on Community Engagement, 2024)
The implementation of the organizing function in pesantren is the implementation of the management function in terms of the distribution of tasks and small activities to be distributed to members according to the expertise of each member of the organization. In the sense that management is in charge of grouping people, responsibilities according to portions so as to achieve the goals of the organization itself together. The Mambaul Huda siliragung Islamic boarding school in Banyuwangi was found to have problems in the management that had dual positions which resulted in a lack of responsibility for their duties and functions. Therefore, it takes a management of Islamic boarding school human resources by formulating the organizational structure. The method used in the implementation of service uses the ABCD (asset-based community development) approach using several strategies, including: 1) Needs analysis 2) active participation in student activities, 3) collaboration with related parties, 4) building relationships with strong teams, 5) developing skills and understanding, 6) evaluation and learning, 7) continuous and sustainable. As for the results of dedication by compiling Service steps, including: understanding of context and objectives, observation and communication with stakeholders, identification of problems and needs, preparation of service plans, collaboration with related parties, implementation of service activities, evaluation and reflection, sharing results and learning, sustainability and follow-up. Conclusion: The management of the main duties and functions and responsibilities in human resources (management) at the Mambaul Huda siliragung Islamic boarding school in Banyuwangi has a major impact on the success and effectiveness of students in the learning process and development. This maintains the continuity of the Islamic boarding school and ensures that students can achieve success as well as the pesantren can achieve success in accordance with the goals and expectations of the pesantren.